Permanence and Periodic Solutions for a Two-Patch Impulsive Migration Periodic N-Species Lotka-Volterra Competitive System - Zijian Liu; Chenxue Yang (Discrete Dynamics in Nature and Society)
We study a two-patch impulsive migration periodic N-species Lotka-Volterra competitive system. Based on analysis method, inequality estimation, and Lyapunov function method, sufficient conditions for the permanence and existence of a unique globally stable positive periodic solution of the system are established. Some numerical examples are shown to verify our results and discuss the model further.